Gerakan bangga buatan Indonesia VS gempuran produk impor: Dilema identitas nasional konsumen digital - Chafidh, Tabina Afra Liyudhza (Maliki Interdisciplinary Journal, 2026)
The National Movement for Proud of Indonesian Products (Gernas BBI) aims to drive MSMEs’ digitalization and economic nationalism, but faces challenges from cheap imports on e-commerce. This asymmetric competition triggers an Intention-Behavior Gap among consumers. This study analyzes the role of social identity in moderating consumer behavior using Social Identity Theory. The results show that consumers experience cognitive dissonance and utilize rational justifications when purchasing foreign goods for utility. It concludes that economic sovereignty cannot rely on pity-based marketing. The solution is transforming strategies into pride-based marketing, establishing local products as modern status symbols, supported by protective government regulations and MSMEs’ technological efficiency.